Challenges to graphene growth on SiC(0 0 0 1‾): Substrate effects, hydrogen etching and growth ambient. (January 2015) - Robinson, Zachary R.; Jernigan, Glenn G.; Currie, Marc; Hite, Jennifer K.; Bussmann, Konrad M.; Nyakiti, Luke O.; Garces, Nelson Y.; Nath, Anindya; Rao, Mulpuri V.; Wheeler, Virginia D.; Myers-Ward, Rachael L.; Wollmershauser, James A.; et al.
Abstract: Controlling the uniformity and morphology of graphene grown on the C-face of SiC is more difficult than on the Si-face. To improve graphene grown on the C-face, a continuous growth process was developed in a conventional tube furnace that included in situ surface preparation by annealing in H2 followed by an Ar-mediated growth, which was done at a variety of different temperatures and pressures. Optimized H2 etch conditions for the C-face were developed to improve the starting substrate morphology and reduce the effect of substrate defects on growth. The resulting graphene film, however, had non-uniform thickness due to intrinsic bulk defects within the SiC substrate and an interfacial oxide. Differences between substrate properties, such as polytype, are shown to have a significant effect on growth, with a 4H substrate displaying faster in-plane graphene growth than a 6H substrate. A primarily 2-domain graphene film with significant rotational disorder was found regardless of the starting substrate and growth conditions. Ultra-high vacuum desorption of the interfacial oxide caused the graphene to reorder into a single preferred rotational orientation, suggesting trace oxygen impurities in the growth chamber can play an important role in graphene growth on the C-face of SiC.